ID 420 – Are sleep spindles inhibitory for pain? A high-density electrophysiological study. Issue 3 (March 2016) - Claude, L.; Callegari, L.; Perchet, C.; Mazza, S.; Garcia-Larrea, L.; Bastuji, H.
Abstract : Sleep spindles are commonly thought to have a sleep-protecting role by inhibiting sensory inputs. However, our previous studies using laser stimuli suggest that spindles may not inhibit the sensory evoked response to nociceptive input. Here, we assessed whether the stimulus occurrence within or immediately close to a spindle could modulate the evoked response to somatosensory electrical stimuli at nociceptive intensity. To increase the number of delivered stimuli during the whole night, we used a concentric planar electrode. Unlike laser they activate A ® rather than the A™ fibres. Experiments were conducted using surface high-density recordings (128 electrodes) and electrical stimuli through concentric planar electrodes at nociceptive intensities in 10 healthy subjects. Cortical responses were analysed in sleep stage N2, according to whether the stimuli were delivered at the beginning, middle or end of a spindle, and just before or following it, or away from it. Cortical evoked responses remained unchanged in latency, amplitude and topography whatever the stimulus condition. These findings confirm the lack of inhibition of nociceptive processing by sleep spindles, at least during the first second following the stimulus. The inhibitory role of spindles on sensory information processing has to be revisited.